FIGURE 3 in A new species and new records of Lecanora (Lecanoraceae, lichenized Ascomycota) with usnic acid from the Antarctic region - Rosa, Iris Nadia De La; Passo, Alfredo; Rodríguez, Juan Manuel; Chiapella, Jorge Oscar; Messuti, María Inés (Zenodo, 2016)
FIGURE 3. Habitus of the new records of Lecanora in the Antarctica. A. L. intricata (BCRU 5385). B. L. stenotropa (BCRU 5380). Scale = 1 mm. Published as part of Rosa, Iris Nadia De La, Passo, Alfredo, Rodríguez, Juan Manuel, Chiapella, Jorge Oscar & Messuti, María Inés, 2016, A new species and new records of Lecanora (Lecanoraceae, lichenized Ascomycota) with usnic acid from the Antarctic region, pp. 185-193 in Phytotaxa 261 (2) on page 190, DOI:10.11646/phytotaxa.261.2.8, http://zenodo.org/record/13672160